Lymphedema Research Prioritization Partnership: A Collaborative Approach to Setting Research Priorities for Lymphedema Management - Underwood, Emma (Lymphat Res Biol, 2019)
Background: More research is needed in lymphedema management to strengthen the evidence base and ensure patients receive clinically and cost-effective treatment. It is critical that patients and clinicians are involved in prioritizing research to ensure that it reflects their needs and is not biased by commercial interests. This study aimed to set the research priorities for lymphedema management in the United Kingdom, through collaboration with patients, carers, and clinicians. Methods and Results: Following the James Lind Alliance's methodology, a national survey was conducted to identify unanswered questions about lymphedema management from the perspective of patients, carers, and clinicians. These were collated and verified against an in-depth evidence review. Unanswered questions were formatted into broad research questions, which were prioritized by a purposive sample of patients, carers, and clinicians, using an online Delphi survey. The initial survey generated 631 submissions from 213 participants, including 108 patients, 9 carers, and 88 clinicians. Of these, 485 met inclusion criteria and were grouped into 12 overarching themes. The evidence review demonstrated that 101 submissions were answered by existing research and identified an additional 78 questions. The remaining unanswered submissions were collated into 126 broad research questions, which were prioritized over four rounds of the Delphi survey to produce the top 10 priorities. Conclusions: This study is the first to attempt to systematically identify research priorities for lymphedema management in the United Kingdom, from the perspective of patients, carers, and clinicians. The results provide guidance for researchers and funders to ensure future research meets the needs of those living with lymphedema.